Polska eseistyka o malarstwie i fotografii od 2. połowy XX wieku w świetle rozważań nad esejem jako formą (pisarstwa, poznania, doświadczania…) - Lisak-Gębala, Dobrawa (Przestrzenie Teorii, 2014)
Contemporary Polish essays on paintings and photographs (by, e.g. Z. Herbert, G. Herling-Grudziński, W. Karpiński, J. Pollakówna, E. Bieńkowska, A. Olędzka-Frybesowa, and W. Nowicki) are juxtaposed with the personal essay which was invented by Montaigne. A wide range of commentaries, including ideas about this genre which were expressed by Th. W. Adorno, G. Lukács, and G. Douglas Atkins, provide a theoretical background for the analysis. Selected Polish texts are presented as artistic constructions that recreate the process of experiencing pictures and the movement of thoughts of the essayistic “self” which uses many disguises (e.g. a traveler, amateur, scholar and critic). A particular painting or photo, which is often artfully described by means of ekphrasis, is treated by essayists as a starting point for analyzing many broader issues as well as for indirect self-presentation.